IMPROVING THE STUDENTS’ SPEAKING IN ARGUMENTATIVE TEXT BY USING INSTAGRAM AS A MEDIA - Ameesha salsabila mesha; Misnawati Misnawati (Journal of English Education and Social Science, 2023)
This study aims to determine the effect of Instagram in improving students' speaking skills. This research used collaborative classroom action research. The objective of this study are: 1) Finding out how Instagram can improve the speaking skill of the students, and 2)Knowing the student respond of the second grade student toward the implementation of the Instagram in improving students speaking skills. To collect data, the researcher used Instruments of observation, test and questionnaire. The finding showed that the used of Instagram was effective in improving students speaking skill of the students in the class. This can be seen from the improvements after each cycle. The average score of the first cycle was 64.25 to 81.66 in the second cycle. The questionnaire instrument received a very positive response to the implementation of Instagram in improving students' speaking skills. Therefore, it can be concluded that Instagram platform can improve students’ speaking skill and also can improve speaking classroom into a better situation. Keyword: Improving, Speaking, Instagram. ​